Pengelolaan Lingkungan di Masjid dan Mushola: Pembuatan Lubang Resapan Biopori dan Pengelolaan Sampah di Desa Lebung Nala - Pratiwi, Dona Dinda; Hibrizi, Diva Syawal; Feriani; Muzakky, Hasyim; Raihan, Muhammad Alfen Ibnu (WISE Pendidikan Indonesia, 2024)
This study aims to identify issues in water and waste management in Lebung Nala Village, Ketapang District, South Lampung Regency, and implement solutions based on Borehole Infiltration (BI) and waste management. The research consists of two main activities: socialization and the construction of BI, both conducted using a participatory approach involving the local community. This participatory approach seeks to raise awareness about the importance of sustainable water and waste management, while empowering the community to apply solutions that address environmental problems such as water stagnation and waste pollution around mosques and other public facilities in the village. The study uses a qualitative participatory approach with triangulation to collect and analyze data. The findings show a significant increase in the community's knowledge and participation in environmental management, with knowledge improving considerably after socialization and an increase in community involvement in the construction of BI. This research contributes to filling existing gaps, especially regarding the application of Borehole Infiltration in rural environments and empowering communities for better environmental management.